Impact of Satisfaction on Customer Loyalty: Perspectives from the Footwear Industry in Peru - Placido, Juana Maribel Manrique; Llerena, Soledad Janett Mostacero; Rodríguez , Ronald Floriano; Pascacio, Patricia Sofía Osorio; Chacón, Luis Fernando Espejo (Journal of Ecohumanism, 2024)
This study investigates how customer satisfaction influences loyalty within the Peruvian footwear sector. A mixed-methods approach of the Dexplis type was employed, combining the collection of quantitative data through a questionnaire administered to 350 consumers, and qualitative data obtained from 25 interviews, to explore how satisfaction affects emotions, intentions, and behaviours of consumers in this specific context. The findings reveal a significant association between satisfaction and loyalty, supported by a Rho coefficient of 0.872, and a multiple regression model showing 80.1% of the variability in loyalty decisions. Additionally, other factors such as innovation, shopping experience, and after-sales service were identified as having a substantial impact on customer loyalty. In summary, this article not only contributes to the theoretical understanding of the association between customer satisfaction and loyalty, but also offers practical implications for improving customer retention strategies in the Peruvian footwear industry, providing key insights for professionals in the sector in strategic decision-making and in designing more satisfactory and engaging shopping experiences.